Konsep Dasar Kepemimpinan Pendidikan Islam (Studi Literatur) - Marsena, Miftahul; Sesmira, Meli; Asmendri, Asmendri; Sari, Milya (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Leadership, Islamic Education, Quality Education This article aims to understand the concept of leaders in Islam and their role in realizing quality Islamic education. This research uses a qualitative approach with a literature study method. Data collection is carried out systematically by identifying relevant literature through online databases such as Google Scholar and DOAJ. Inclusion criteria include publications relevant to the topic, published within a relatively recent time frame (the last 10 years). Data is analyzed using a descriptive-qualitative content analysis approach. The results of the analysis show that leadership is an essential part that is inseparable from Human Resources (HR). As a captain, a leader is the person who understands best the direction to take. In the context of Islamic education, leadership is fundamental and has significant relevance to the success of education. The role of leadership in realizing excellent education can be executed through exemplary behavior, the application of punishment and rewards to all stakeholders, leadership commitment, and the fulfillment of facilities and infrastructure that support the smooth running of the Islamic education process.